2017
DOI: 10.1155/2017/8789724
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Emotional Expressions after Full-Face Transplantation

Abstract: We assessed clinical features as well as sensory and motor recoveries in 3 full-face transplantation patients. A frequency analysis was performed on facial surface electromyography data collected during 6 basic emotional expressions and 4 primary facial movements. Motor progress was assessed using the wavelet packet method by comparison against the mean results obtained from 10 healthy subjects. Analyses were conducted on 1 patient at approximately 1 year after face transplantation and at 2 years after transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Various methods have quantified motor function recovery, including facial surface electromyography, which found similar high-frequency firing distributions in one-third of patients with full FT as healthy controls during emotional expression testing. 34 Despite providing an objective assessment, widespread adoption is precluded because this modality relies on invasive electrode placement, skilled interpretation, and inability to detect clinically meaningful return of function in patients with FT. 35 Image-based analysis, reporting 45% return of happiness expression after 3 years in two patients with FT, 36 likewise required trained interpretation of results and processed only still frames without capability to assess dynamic function.…”
Section: E Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods have quantified motor function recovery, including facial surface electromyography, which found similar high-frequency firing distributions in one-third of patients with full FT as healthy controls during emotional expression testing. 34 Despite providing an objective assessment, widespread adoption is precluded because this modality relies on invasive electrode placement, skilled interpretation, and inability to detect clinically meaningful return of function in patients with FT. 35 Image-based analysis, reporting 45% return of happiness expression after 3 years in two patients with FT, 36 likewise required trained interpretation of results and processed only still frames without capability to assess dynamic function.…”
Section: E Discussionmentioning
confidence: 99%
“…Thus, 13 patients met inclusion criteria (11 male patients; age, 40 ± 14 years); eight received all AUs with full FT and five underwent partial FT receiving AUs of the midface and lower two-thirds of the face (Table 1). 4,7,28,[34][35][36][37][38][39][40] Mean donor allograft and healthy control age were 40 ± 13 years and 41 ± 11 years, respectively (P = 0.933). Mean video follow-up time was 3.6 ± 2.2 years.…”
Section: Study Participant Characteristicsmentioning
confidence: 99%
“…Some studies have attempted to measure emotional expression after face transplant. Topçu et al 15 found that the frequency and spatial distribution of facial surface electromyography data recorded during emotional expression were significantly different between patients with face transplants and healthy controls after 2 years. One of their 3 patients with full face transplants had high-frequency firing distribution similar to that of healthy controls for happiness, whereas other expressions had similar distribution patterns but lower frequency.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Despite their high relevance, limited quantitative data are available on the restoration of facial emotional expression after face transplant. Existing evidence comes from methods such as facial surface electromyography, 15 which is sensitive but requires painstaking placement of several electrodes on the skin, 16 and appearance-based facial feature extraction, which is similar to facial recognition technology but requires significant data processing that limits reproducibility. 17 These methods are obtrusive and prone to human instrumentation error.…”
Section: Introductionmentioning
confidence: 99%
“…Primary motor and sensory innervations of the transplanted faces of individuals are usually complete within 9 months (Topçu et al, 2017). However, this course involves the loss of face tissue, as the muscle and skin innervation of the face tissue undergoes the process of total denervation and reinnervation (Özkan et al, 2017; Siemionow et al, 2011a).…”
mentioning
confidence: 99%